IMPLEMENTASI PROGRAM MAGANG MAHASISWA SEBAGAI BENTUK PENGABDIAN MASYARAKAT DALAM MENDUKUNG EFEKTIVITAS OPERASIONAL BACK OFFICE PERBANKAN DI PT BANK RAKYAT INDONESIA UNIT BENGKAYANG - Elysabet Elysabet; Devi Meliani Irene; Deffrinica Deffrinica (Jurnal Pengabdian Bukit Pengharapan, 2026)
The internship program is an integral part of the learning process that provides students with practical work experience relevant to their field of study. This article aims to describe the implementation of the internship program in supporting the effectiveness of Back Office operations at PT Bank Rakyat Indonesia (Persero) Tbk Unit Bengkayang. The study employed a descriptive method through direct workplace practice, involving students in various Back Office operational activities, including Customer Information File (CIF) data entry, collateral registration and document management, BRIMEN administration, ASMIK (insurance) administration, customer service, and cash verification. The results indicate that the internship program contributed to smoother administrative operations, improved accuracy in data and document management, and enhanced the effectiveness of customer service. In addition, the internship enabled students to develop administrative, communication, accuracy, and responsibility skills while adapting to a professional working environment. Therefore, the internship program provides valuable benefits for both the institution and students by supporting effective Back Office operations and strengthening students' professional competencies.